ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY AND TRUST ON GOLD PAWN CUSTOMER SATISFACTION - Nur'aeda, Nur'aeda; Tulhasana, Lisman (Laboratorium Riset Ekonomi, 2025)
This study aims to analyze the influence of service quality and trust on customer satisfaction in the gold pawn service at Bank Syariah Indonesia (BSI) KCP Sape, Bima Regency. Service quality and trust are considered two critical factors that significantly affect the satisfaction level of customers using sharia-based financial services. The study uses a quantitative descriptive method with data collected through questionnaires distributed to 93 respondents. The results of multiple linear regression analysis indicate that both service quality and trust have a positive and significant influence on customer satisfaction. The coefficient of determination (R²) of 0.972 shows that 97.2% of the variation in customer satisfaction can be explained by these two variables. Furthermore, the findings from the t-test and F-test confirm the significant effect of service quality and trust, both partially and simultaneously, on customer satisfaction. This research highlights the importance for Islamic financial institutions to enhance service quality and build customer trust to improve overall satisfaction and competitive advantage.